Strategies to Improve School Readiness to Accept Students with Special Needs through Inclusive Education - Afriani, Gusma; Fransiska, Fini Widya; Krisnawati, Nova (Global Education Journal, 2025)
Inclusive education is increasingly recognized as a vital approach to ensuring equal access to quality education for all students, including those with special needs. However, many schools remain unprepared to implement inclusive practices effectively due to limited resources, lack of training, and insufficient systemic support. This research aims to explore strategies that can increase school readiness in accepting students with special needs through inclusive education. Using a qualitative research design, the study was conducted in three inclusive elementary schools in Indonesia over a three-month period. Data were collected through in-depth interviews, participant observation, and document analysis, involving teachers, principals, special education coordinators, and parents. The findings reveal that teacher professional development, inclusive school leadership, adaptive learning environments, and strong parent-community engagement are key strategies that enhance readiness. Furthermore, the study highlights a positive shift in teacher attitudes through experience and reflection, promoting a more inclusive school culture. The conclusion emphasizes that readiness is not only a structural issue but also a cultural and attitudinal transformation process. This research contributes to the development of practical models for inclusive education in resource-constrained settings and provides valuable insights for policymakers, educators, and advocates aiming to foster more equitable and supportive learning environments.